FCRL1 immunoregulation in B cell development and malignancy - Mamidi, Murali K.; Huang, Jifeng; Honjo, Kazuhito; Li, Ran; Tabengwa, Edlue M.; Neeli, Indira; Randall, Nar’asha L.; Ponnuchetty, Manasa V.; Radic, Marko; Leu, Chuen-Miin; Davis, Randall S. (Frontiers in Immunology, 2023)
Immunotherapeutic targeting of surface regulatory proteins and pharmacologic inhibition of critical signaling pathways has dramatically shifted our approach to the care of individuals with B cell malignancies. This evolution in therapy reflects the central role of the B cell receptor (BCR) signaling complex and its co-receptors in the pathogenesis of B lineage leukemias and lymphomas. Members of the Fc receptor-like gene family (FCRL1-6) encode cell surface receptors with complex tyrosine-based regulation that are preferentially expressed by B cells. Among them, FCRL1 expression peaks on naïve and memory B cells and is unique in terms of its intracellular co-activation potential. Recent studies in human and mouse models indicate that FCRL1 contributes to the formation of the BCR signalosome, modulates B cell signaling, and promotes humoral responses. Progress in understanding its regulatory properties, along with evidence for its over-expression by mature B cell leukemias and lymphomas, collectively imply important yet unmet opportunities for FCRL1 in B cell development and transformation. Here we review recent advances in FCRL1 biology and highlight its emerging significance as a promising biomarker and therapeutic target in B cell lymphoproliferative disorders.